Morphology of Islamic Traditional Iraqi Courtyard House Toward Holistic Islamic Approach in New Residential Development in Iraq - Jawad Shakir Haraty, Hayder; Yazah Mat Raschid, Mohammad; Yazid Mohd Yunos, Mohd (International Journal of Engineering and Technology, 2018)
The traditional Iraqi house represents the ideal living style of its occupants. Its exceptional form has been designed to respond to the Islamic social and cultural needs of the house residents. The people behaviors have magnificently shaped the architecture identity of Iraq. By the time, the dilemma of traditional courtyards house appeared in the 20th century after numerous consequences causing the terrifying disappearance of this monument. Not only the lack of understanding the Islamic function of this traditional house but also the new modern designs of housing have been missing the identity of Iraq architecture. The urgent demand is to investigate the remaining cases of traditional courtyards house, and its function as Islamic space to emerge to the new housing applications in Iraq. Additionally, this study is focusing on the way that the courtyards house function and embrace certain Islamic elements that could be utilized to the new modern houses. Therefore, a morphological study has been carried out with the intention of analyzing the planning form and physical characteristics of two traditional Iraqi dwellings. The study has gone some way toward understanding that the courtyard house in Iraq does hold meaningful Islamic principles that implemented in its design physically and in its form. Accordingly, it empathizes the main reason that this kind of houses has been ideal is that it flourished from people culture and necessities over the years. The result of this study enhances the architecture design of the current and future worldwide Muslims houses into more expressive manners.Â Â